Contested heritage : an analysis of the discourse on The spirit sings - Archibald, Samantha L.; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Faculty of Arts and Science , 1995, 1995)
vi, 335 p. 29 cm. This thesis contributes to the knowledge of museology, anthropology and Native American studies. It is an analysis of the discourse that surrounded The Spirit Sings: Artistic Traditions of Canada's First Peoples, an exhibition prepared by the Glenbow in Calgary as the 'flagship' of the Olympic Arts Festival in 1988. After the Lubicon Indians of Northern Alberta called for a boycott of The Spirit Sings, in attempt to draw critical attention to their long outstanding lands claim, a large and heated debate ensued involving several disciplines, particularly anthropology and museology. Much of this debate took place in the print media, therefore a large body of material remains to be reviewed and studied. The intent of this thesis is to illustrate that the issue of museological representation of First Nations was one of the most central themes discussed in the discourse, but to argue that the major players dealt with this issue on only the most concrete level and therefore largely neglected to recognize that the issue of First Nation's representation was not just a concern over museum interpretation but more importantly an issue of the contested authenticity of national and cultural claims.